Cover Image, Volume 42, Issue 6. Issue 6 (14th June 2022) - Leng, Ling; Liu, Zhaorui; Ma, Jie; Zhang, Shiyu; Wang, Yukun; Lv, Luye; Zhu, Yunping; Gao, Dunqin; Wang, Yujie; Wang, Juncheng; Liu, Yuehua; Liu, Jie
Abstract : The cover image is based on the Letter to Editor Proteomic identification of new diagnostic biomarkers of early‐stage cutaneous mycosis fungoides by Ling Leng et al., https://doi.org/10.1002/cac2.12266 .